Comparison of Sleep Quality Between Acupuncture Therapy and Blue Pela Flower Tea in Adolescents: A Randomized Controlled Trial - Latifah, Shafa; Prasetya, Hanung; Murti, Bhisma (Indonesian Journal of Medicine, 2024)
Background: Reduced sleep quality will have an impact such as decreased concentration, emotional disturbances, health and daily activities. There are several factors outside of puberty (hormonal) that cause the percentage of insomnia sufferers to be higher among adolescents, including lifestyle and environment which are the causes of insomnia in adolescents. Positive findings have been found in a study reporting that acupuncture and herbal butterfly pea flower tea can improve patient health and sleep quality. This study aims to determine the comparison of acupuncture therapy and herbal butterfly pea flower tea. Subjects and Method: This study is a quantitative study with a Randomized Controlled Trial (RCT) design. This study was conducted at SMKN 5 Merangin in March-April 2024. A sample of 120 students was selected using simple random sampling. The dependent variable in this study is sleep quality in cases of insomnia. The independent variables in the study are acupuncture therapy and butterfly pea herbal tea. Result: The best intervention for improving sleep quality was acupuncture (Mean= 3.65; SD= 1.12), which was better than butterfly pea tea (Mean= 2.13; SD= 1.09) or nothing (Mean= 0.20; SD= 1.20), and the difference between the groups was statistically significant (p<0.001). Conclusion: The best intervention to improve sleep quality was acupuncture compared to butterfly pea herbal tea.